Interrelations between polymorphism of a gene of a methylenetetrahydrofolatreductase with level of Homocystein in patients with 2 type of diabetes - Alina, A.R.; Turgunova, L.G.; Laryushina, Ye.M.; Vasilyeva, N.V.; Amirkhanova, D.T. (KSU publ., 2015)
Purpose of the research — to study the frequency of occurrence of polymorphism ST gene methylenetetrahydrofolate patients with diabetes mellitus type 2 and its correlation with homocysteine levels and the development of ischemic heart diseases. 118 patients with diabetes mellitus type 2 at the age of 45–60 years were surveyed. Statistically significant differences were observed frequencies of alleles of T and S, genotype SS between groups of patients with pancreatic diabetes type 2 with ischemic heart disease and tran- sferred myocardial infarction and healthy persons. It was found that the allele T 677 gene, methylentetrahydrofolatreductase associated with an increased risk of myocardial infarction in patients with diabetes mellitus type 2 (OR=1,879, p=0,029). The combination of genotype T677 gene methylenetetrahydrofolatereductase with hyperhomocysteinemia in 2 type diabetic patients with coronary heart disease is related with other risk factors for cardiovascular diseases and can have a significant impact on the course of ischemic heart disease.
Диабеттің 2-түрінде метилентетрагидрофолатредуктаза гені полиморфизмінің гомоцистеин деңгейімен өзара байланысы
Взаимосвязь полиморфизма гена метилентетрагидрофолатредуктазы с уровнем гомоцистеина при сахарном диабете 2 типа
Keywords: diabetes mellitus type 2; coronary heart illness; homocysteine; methylenetetrahydrofolate